Information sharing and the use of Web 2.0 technologies for educational purposes by undergraduates of two Universities in Ibadan, Nigeria (2018)
Availability of learning material online, online discussion forum and online testing often support and complement face to face teaching and learning. This has shifted focus from teacher-centred to student-centred learning: this is facilitated with the use of Web 2.0 tools, it is therefore necessary for students nowadays have a firm understanding of computer technology> and its various applications to share information necessary for their educational purposes. Students sharing ideas is not new with the advent of Web 2.0 technologies. Students have long been swapping comments in tutorial, chatting and debating in classrooms. But with the use of the web it becomes a lot easier since the goal of the web is to facilitate easier. dissemination of educational information to a wider audience. The study examined information sharing and use of web 2.0 for educational purposes by undergraduates. The study recommended that there is the need for institutions to train students on the use of Web 2.0 technologies tools and applications to enable them identify the necessary- applications which help to meet their information needs. Students need to be sensitized on the various benefits of the use of web 2.0 for academic purposes. Faculties, departments and libraries should endeavour to provide functional and high-speed internet access for students. Institutions can develop Web 2.0 technologies application that can assist students with their academic work as well as serve as an avenue for exchange of information and entertainment